2022
DOI: 10.3389/fmed.2022.869320
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surgery in High-Grade Neuroendocrine Cancer: Indications for Clinical Practice

Abstract: Pulmonary neuroendocrine tumors (pNET) represent a particular type of malignant lung cancers and can be divided into well-differentiated low-grade NET and poorly-differentiated high-grade NET. Typical and atypical carcinoids belong to the first group while large cell neuroendocrine carcinomas (LCNEC) and small-cell lung cancers (SCLC) belong to the second one. The aim of this mini-review is to focus on the role of surgical therapy for high grade neuroendocrine tumors. SCLC has the worst prognosis among all lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Stage and grade significantly affect patient prognosis [ 15 17 ]. A higher stage or grade usually indicates poorer differentiation, greater malignancy, and tremendous potential for metastasis, which can affect patient survival [ 18 , 19 ]. As a malignant wasting disease, a higher stage or grade of NEC can cause greater consumption, burden, and impact on the body [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stage and grade significantly affect patient prognosis [ 15 17 ]. A higher stage or grade usually indicates poorer differentiation, greater malignancy, and tremendous potential for metastasis, which can affect patient survival [ 18 , 19 ]. As a malignant wasting disease, a higher stage or grade of NEC can cause greater consumption, burden, and impact on the body [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have proposed that complete surgical resection is considered to improve prognosis regardless of the NEN histological type, while LND is necessary for complete resection. This view has gradually reached consensus through extensive clinical practice and research [ 19 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a classical treatment approach, surgical resection has been proven to be associated with extended survival in patients with neuroendocrine carcinoma [ 6 , 14 , 15 ]. Previous studies focused on small-cell lung cancer and reported that patients with stage I-IIA were more appropriate to receive surgery than those with stage IIb-III [ 5 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, with advances in diagnostic and surgical technologies, many researchers have begun challenging the current view of surgery in treating SCLC and have attempted to expand the surgical indications for SCLC. 510…”
Section: Introductionmentioning
confidence: 99%
“…4 However, with advances in diagnostic and surgical technologies, many researchers have begun challenging the current view of surgery in treating SCLC and have attempted to expand the surgical indications for SCLC. [5][6][7][8][9][10] In the present study, we explored the value of surgery in treating SCLC. We identified relevant prognostic factors in the hope of clarifying the significance of surgery in the prognosis of SCLC patients and reassessing its importance in the multi-disciplinary treatment of SCLC.…”
Section: Introductionmentioning
confidence: 99%